2017
DOI: 10.1371/journal.pone.0186449
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic therapy strategies for atrial fibrillation patients undergoing percutaneous coronary intervention: A systematic review and network meta-analysis

Abstract: ObjectiveThe aim of this systematic review and network meta-analysis was to evaluate the comparative efficacy and safety of antiplatelet agents, vitamin K antagonist (VKA) and non-VKA oral anticoagulants (NOACs) in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI).MethodsPubMed, EMBASE, and the Cochrane Central Register of Controlled Trials were searched to identify clinical trials comparing antiplatelet drugs with VKA and NOACs or their combination in AF patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…A prior NMA investigated antithrombotic strategies in patients with AF and ACS and/or PCI. The authors found that the combination of VKA and a single antiplatelet agent provided the best choice in terms of safety and efficacy, with a very low dose of rivaroxaban, 2.5 mg, twice daily plus DAPT as an acceptable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…A prior NMA investigated antithrombotic strategies in patients with AF and ACS and/or PCI. The authors found that the combination of VKA and a single antiplatelet agent provided the best choice in terms of safety and efficacy, with a very low dose of rivaroxaban, 2.5 mg, twice daily plus DAPT as an acceptable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…AF: atrial fibrillation trial-like strategy was chosen, which is also supported by a meta-analysis that suggests that a combination of vitamin K antagonists and single antiplatelet therapy is the best choice for AF patients undergoing percutaneous coronary intervention (PCI) considering both efficacy and safety. 16,17 Stenestrand et al 18 and Lopes et al 15 showed that only a small percentage of patients with AF and acute MI received oral anticoagulation therapy at discharge (30% and 43.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, a strategy based on NOACs was associated with a reduced risk of major bleeding events 51,52 . However, a network meta-analysis concluded that the best treatment strategy for these high-risk patients still appears to be the use of a VKA and single antiplatelet drugs when considering both efficacy and safety, even though the use of low-dose rivaroxaban appears as a valid alternative 53 .…”
Section: Summary and Discussionmentioning
confidence: 99%